Limitations of faecal chymotrypsin as a screening test for chronic pancreatitis. Issue 3 (March 1991) - Riedel, L; Walker, A R; Segal, I; Mohamed, A E; Smyth, A E; Daya, B; Naik, I
Abstract : Faecal chymotrypsin was measured in patients with chronic pancreatitis and in healthy black urban and rural control subjects. In the patients, significantly lower values of faecal chymotrypsin were obtained (mean (SD) 2.4 1.79 U/g stool) whereas in urban control subjects, values were within the normal range (mean (SD) 13.2 (11.9)). In rural black control subjects, however, the faecal chymotrypsin value was significantly lower (mean (SD) 7.1 (5.1)) than in urban black control subjects. It is suggested that faecal pH may influence faecal chymotrypsin values. The mean faecal pH in rural black subjects (pH 6.14) was significantly lower than that in urban control subjects (pH 6.77) and in patients with chronic pancreatitis (pH 6.61). Moreover, mean faecal chymotrypsin is high (20.0 U/g stool) at a pH greater than 7. Between pH 6 and 7 the mean value drops to 8.6 U/g stool and below pH 6 mean faecal chymotrypsin is in the abnormal range (4.4 U/g stool). Hence, low values for faecal chymotrypsin may be due to lower faecal pH (less than 6) in healthy control subjects. For diagnostic purposes, the faecal pH value should be determined if a low faecal chymotrypsin value is obtained.